2019
DOI: 10.32929/2446-8355.2019v28n2p194-203
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de soja, sob interferência de plantas infestantes

Abstract: A competição entre os recursos ambientais, imposta pela comunidade infestante, afeta o crescimento, produtividade e qualidade final da soja, prejudicando a colheita, por competição, que aumenta o custo operacional. Outro fator relevante da interferência das plantas infestantes é que estas podem ser hospedeiras de patógenos e pragas, o que dificulta seu controle. Este trabalho teve como objetivo avaliar o desempenho agronômico de duas cultivares de soja sujeitas à interferência de plantas infestantes. O experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 7 publications
4
8
0
7
Order By: Relevance
“…In contrast, the more significant growth of soybean plants, verified in the evaluation performed at 14 DAE in the treatments weeded after 20 DAE and without weeding, about the treatments weeded throughout the entire cycle and weeded up to 20 DAE, is a result of competition for light. This provoked the etiolation of the plants due to the shading imposed by the weeds, as reported in previous research [9,19].…”
Section: Resultssupporting
confidence: 75%
“…In contrast, the more significant growth of soybean plants, verified in the evaluation performed at 14 DAE in the treatments weeded after 20 DAE and without weeding, about the treatments weeded throughout the entire cycle and weeded up to 20 DAE, is a result of competition for light. This provoked the etiolation of the plants due to the shading imposed by the weeds, as reported in previous research [9,19].…”
Section: Resultssupporting
confidence: 75%
“…The soybean cultivar DM 66i68 showed concave lines for RP and TRP, both for LA and DM, and values less than 1 in all simulations performed, which demonstrates its genetic differentiation in relation to the other cultivars (Table 1). Differentiation in competitive ability when involving soybean cultivars with weeds was also observed in early-cycle and late-cycle soybean cultivars (SOUZA et al 2019), and between soybean cultivars V-TOP RR and BMX Ativa RR (DIESEL et al 2020). Furthermore, HAMMER et al (2018 found that, among 40 soybean cultivars, the most modern and with the highest production capacity were more competitive in relation to older cultivars in a highly competitive environment.…”
Section: Resultsmentioning
confidence: 76%
“…Thus, it is possible to affirm that when the crop and weeds are in early stages of development, there is no harmful competition for these individuals (Zandoná et al, 2018), which can be considered the period before interference. However, monitoring the crop since the emergence, through weed control in early stages, ensures better control of the infesting population (Agostinetto et al, 2009), considering that the increase of density of these plants, especially those of that develop at the beginning of the crop cycle, accentuate the competition for water, light and nutrients (Souza et al, 2019). The critical period of interference extended from 20 to 50 days.…”
Section: Resultsmentioning
confidence: 99%